AN ANALYSIS OF TRANSLATION METHOD FROM INDONESIA TO ENGLISH IN INDONESIA SONGS “ CINTANYA AKU” COVERED BY EMMA HEETERS - Iman Kristiani Gulo; Agnes Foneria Zebua; Tantri Aurelia Gulo; Anatasya Novanda Aritonang (Journal of Language Education (JoLE), 2025)
This research examines the translation techniques employed in the English version of the Indonesian song "Cintanya Aku", performed by Dutch artist Emma Heesters. Music translation requires maintaining linguistic meaning alongside artistic aspects like emotion, rhythm, and cultural context; thus, this study utilizes Peter Newmark’s translation theory to analyze and categorize the employed methods. Employing a qualitative descriptive method, the researchers analyzed the original Indonesian lyrics (source language) alongside their English translation (target language). The analysis indicates that Emma Heesters' translation mainly employs communicative and literal methods, along with supplementary uses of semantic and free translation techniques. The results indicate that the translation approach emphasizes emotional transparency and cultural reach for English-speaking viewers, in line with the principle of domestication. This guarantees that the lyrical elements continue to be emotionally impactful and contextually appropriate in the desired language. Ultimately, the research emphasizes the significance of strategic translation methods in cross-cultural music adaptation.